2013
DOI: 10.7126/cdj.2012.1030
|View full text |Cite
|
Sign up to set email alerts
|

Diş hekimlinde lokal anesteziklere bağlı allerji

Abstract: <p><strong>Objectives: </strong>Dental treatment of many patients is delayed owing to a positive history of allergic reactions.<strong> </strong>The aim of this study is to retrospectively investigate the results of local anaesthetic allergy tests of the patients, who were sent for allergy consultation due to their history of allergic reactions, and the following dental treatments carried out under local anaesthesia in the Department of Oral Surgery, School of Dentistry, Ege Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…None of the 5 patients with a history of local anesthetic allergy had a positive ID test. Similar to the litera-ture, none of the 10 patients with a history of allergies to local anesthetics were found to be positive (12). In a retrospective study of 5018 patients treated with local anesthesia, the incidence of adverse effects was found as 0.5%.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…None of the 5 patients with a history of local anesthetic allergy had a positive ID test. Similar to the litera-ture, none of the 10 patients with a history of allergies to local anesthetics were found to be positive (12). In a retrospective study of 5018 patients treated with local anesthesia, the incidence of adverse effects was found as 0.5%.…”
Section: Discussionsupporting
confidence: 58%
“…Although allergic reactions due to local anesthetics are more frequent in the ester group, its use in dentistry is reduced. As a result, complications due to local anesthetics are rare (11,12). In our study, 86.5% patients did not have any allergies according to prick test and subsequent intradermal test results.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Cağıran et al [19] reported that only one of 30 patients in whom allergy consultation was requested before intervention because of a history of atopic disease or drug allergy had a positive test result. Although rare in the literature, allergic reactions following LA injections may develop due to preservatives (methylparaben)…”
Section: Figure 1 Local Anesthetics Preference According To the Titlesmentioning
confidence: 99%